The major factors of influence on the socio-psychological climate in the team of health care workers. - T. A. Vezhnovets (Medičnì Perspektivi)
The aim of the research was to identify the major factors that can positively or negatively effect the state of the socio-psychological climate in the medical team of healthcare institutions. The psychological study of the social-psychologic climate of 152 health care workers of two hospitals of Kherson region (N 1, n=80; N 2, n=72) was conducted. It is established that the level of self-esteem of climate in the institution №1 was significantly lower than in institution N 2 (р<0,007). Moreover, these two institutions differed significantly by experience of joint work of health workers (р<0.05) and length of service of the headphysicians. Health care workers with less joint work experience have been working in the institution N 1, and it was headed by the head physician with less leading experience. By the opinion of health workers of both institutions, such factorsas "interesting and meaningful work", "attentive head", "relations with colleagues", have the most positive impact on the state of climate the most negative influence — "unsatisfactory management style", "tensions in the team", "lack of financial motivation", "poor working conditions". Each team has its own combination of factors that positively or negatively affect the state of the climate. It is established, that depending on the work experience of the head physician and the work experience of joint work of employees, the main factors that affect the climate in the team are "attentive manager" and "relationships with colleagues". The more work experience of the leader, the more it will affect the state of the climate in the team. The less experience of joint work of employees, the more "relationship with colleagues" will affect its condition. Evaluation of the state of socio-psychological climate and its factors by the personnel may be the indicator of efficiency of personnel management in the health care institution.